2018
DOI: 10.1097/aog.0000000000002572
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Implementation of Pharmacist-Prescribed Hormonal Contraceptives in California

Abstract: In the first year after statewide protocol implementation, only a small proportion of retail pharmacies across California has begun offering hormonal contraception services. In the absence of additional supportive legislation regarding reimbursement for pharmacist services, increases in scope of practice regulations to build a larger network of contraceptive providers may not be effective in increasing access to birth control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 18 publications
0
13
2
Order By: Relevance
“…23 Recent studies of pharmacies in California demonstrate that 5%-11% of pharmacies have implemented pharmacist prescribing of contraception within the first year. 3,24 A 2015 survey of Oregon pharmacists showed that 57% were interested in prescribing contraceptives, but only 39% planned to participate. 25 Those practicing in urban settings and those currently providing emergency contraception were more likely to indicate they planned to prescribe.…”
Section: Methodsmentioning
confidence: 99%
“…23 Recent studies of pharmacies in California demonstrate that 5%-11% of pharmacies have implemented pharmacist prescribing of contraception within the first year. 3,24 A 2015 survey of Oregon pharmacists showed that 57% were interested in prescribing contraceptives, but only 39% planned to participate. 25 Those practicing in urban settings and those currently providing emergency contraception were more likely to indicate they planned to prescribe.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol requires use of a patient self-screening questionnaire to determine eligibility for the various self-administered hormonal contraceptive methods—pill, transdermal patch, vaginal ring, and depot medroxyprogesterone acetate (DMPA) injection. In the first year after protocol availability, 5%–11% of pharmacies were providing the service [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In Oregon, a state in which Medicaid offers and pays for this service, 10% of women with this insurance benefit chose a pharmacy to obtain their new birth control prescriptions [ 26 ]. In California, Oregon, and New Mexico, pharmacists offered birth control prescribing in rural and urban community pharmacies [ 27 , 28 ], which would align with our female college students in rural, small, and urban residences willing to get birth control from a community pharmacist.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacist trustworthiness, approachability, and visit expenses significantly influenced their likelihood of using birth control pharmacists. In the opinion-based studies about pharmacist prescribing, women of all ages would use or support this service, but they do express concerns as well [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Our research adds that prior use of pharmacy services and perceptions of pharmacist attributes influence these opinions.…”
Section: Discussionmentioning
confidence: 99%